Bi-modal stimulation in the treatment of tinnitus: a study protocol for an exploratory trial to optimise stimulation parameters and patient subtyping - D’Arcy, Shona; Hamilton, Caroline; Hughes, Stephen; Hall, Deborah A.; Vanneste, Sven; Langguth, Berthold; Conlon, Brendan (BMJ Publishing Group, 2017)
Introduction: Tinnitus is the perception of sound in the absence of a corresponding external acoustic stimulus. Bi-modal neuromodulation is emerging as a promising treatment for this condition. The main objectives of this study are to investigate the relevance of inter-stimuli timing and the choice of auditory stimuli for a proprietary bi-modal (auditory and somatosensory) neuromodulation device and to explore whether specific subtypes of patients are differentially responsive to this novel intervention for reducing the symptoms of chronic tinnitus. Methods and analysis: This is a two-site, randomised, triple-blind, exploratory study of a proprietary neuromodulation device with a pre-post and 12-month follow-up design. Three different bi-modal stimulation parameter sets will be examined. The study will enrol 342 patients, split 80:20 between two sites (Dublin, Ireland and Regensburg, Germany), to complete 12 weeks of treatment with the device. Patients will be allocated to one of three arms using a step-wise stratification according to four binary categories: tinnitus tonality, sound level tolerance (using Loudness Discomfort Level of <60 dB SL as an indicator for hyperacusis), hearing thresholds, and presence of a noise-induced audiometric profile. The main indicators of relative clinical efficacy for the three different parameter sets are two patient-reported outcomes measures, the Tinnitus Handicap Inventory and the Tinnitus Functional Index, after 12 weeks of intervention. Clinical efficacy will be further explored in a series of patient subtypes, split by the stratification variables and by presence of a somatic tinnitus. Evidence for sustained effects on the psychological and functional impact of tinnitus will be followed up for 12 months. Safety data will be collected and reported. A number of feasibility measures to inform future trial design include: reasons for exclusion, completeness of data collection, attrition rates, patient’s adherence to the device usage as per manufacturer’s instructions and evaluation of alternative methods for estimating tinnitus impact and tinnitus loudness. Ethics and dissemination: This study protocol is approved by the Tallaght Hospital / St. James’s Hospital Joint Research Ethics Committee in Dublin, Republic of Ireland, and by the Ethics Committee of the University Clinic Regensburg, Germany. Findings will be disseminated to relevant research, clinical, health service and patient communities through publications in peer-reviewed and popular science journals and presentations at scientific and clinical conferences. Trial registration number; the trial is registered on ClinicalTrials.gov (NCT02669069). The sponsor is Neuromod Devices, Dublin, Republic of Ireland. STRENGTHS AND LIMITATIONS OF THIS STUDY • The main strength of this study is that it is a large two-site, triple-blinded, randomised trial that will provide exploratory evidence of the relevance of stimulation parameters on the clinical efficacy of different bi-modal stimulation parameters and will inform future trial design. • The study comprehensively characterises patients for subtyping and this will refine candidature for the intervention. • Among the limitations of this study are the variability in duration between screening and enrolment and the selection of the investigated stimulation parameters. • The online recruitment process may inadvertently introduce participant selection bias.